Ozone therapy in traumatology and burns treatment (Ozone Therapy Global Journal, 2013)
This review summarizes the bases of the use of ozone in wound healing in patientssufferin g from trauma or burns. Di fferent clinical assays had shown that lo cal orsystemic application of oxygen-ozone therapy in wounds and superficial scalds resultsin accelerated cleansing of a wound from necrotic tissues without generate necrosis.In addition to the well know germicide effect of ozone, its application can stimulate thelocal tissue regeneration, the local immune response and can control the inflammatoryreaction. The quick management of pain and edema, the reduction of epithelializationtime and the better graft retention are part of the benefit of the integrative use of ozonein traumatology and burns treatment.Bases on the Russ ian clinical experience the indication, contrai ndication, protocolsand specific care during the application of this therapy was described. The systemicozone therapy conducted af ter an analy sis of the oxidative str ess status in thosepatients was referred. The concept of integration of ozone therapy as part of the routingcare of the wounds is expressed. In this context the application of ozone offer manyadvantages, for instance: ozone reactivating the oxygen homeostasis, can increasethe antioxidant ac tivity of blood pla sma, im prove periph eral circu l atio n andmicrocircu l atio n, induce homeost asis compens ation, and modulate the antiinflammatoryand immune response in addition to their detoxification effects